2022
DOI: 10.3390/nu15010146
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Diet Quality during Pregnancy and Allergic and Respiratory Multimorbidity Clusters in Children from the EDEN Mother–Child Cohort

Abstract: We investigated the associations between maternal diet quality and allergic and respiratory diseases in children. Analyses were based on 1316 mother–child pairs from the EDEN mother–child cohort. Maternal diet quality during pregnancy was assessed through a food-based score (the Diet Quality), a nutrient-based score (the PANDiet), and the adherence to guidelines for main food groups. Clusters of allergic and respiratory multimorbidity clusters up to 8 years were identified using Latent Class Analysis. Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Then, negative associations could be explained by the potential beneficial effect of high intake of fruit and vegetable on asthma, as reported in general population [ 26 ]. However, the protective effect of fruit consumption during pregnancy on asthma and respiratory events in offspring is not well established [ 17 ]. Moreover, in our study the mixture composed by perfluoroalkyl acids, PAHs and trace elements was not strongly correlated with any individual food item.…”
Section: Discussionmentioning
confidence: 99%
“…Then, negative associations could be explained by the potential beneficial effect of high intake of fruit and vegetable on asthma, as reported in general population [ 26 ]. However, the protective effect of fruit consumption during pregnancy on asthma and respiratory events in offspring is not well established [ 17 ]. Moreover, in our study the mixture composed by perfluoroalkyl acids, PAHs and trace elements was not strongly correlated with any individual food item.…”
Section: Discussionmentioning
confidence: 99%
“…Willers et al found that maternal apple intake during pregnancy was associated with lower wheezing and asthma among offspring at ve years old [8]. Another study found that children born to mothers who consumed legumes once a month or less were at a heightened risk of belonging to the 'multi-allergic' cluster, suggesting a potential role for legume consumption in preventing allergic diseases [30]. A third study observed an association between maternal intake of peanuts and tree nuts and the prevalence of asthma in 18-month-old toddlers [31].…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of specific foods during pregnancy has been linked to the development of atopic conditions [ 74 ], yet these studies have failed to establish such a link to food allergy development. Greater maternal consumption of processed foods during pregnancy has been correlated with increased food allergy in infants [ 75 , 76 ].…”
Section: Dietary Factors In Allergic Diseasementioning
confidence: 99%